The Moderating Effect of Brand Architecture on the Relationship Between Tangibility and Customer Loyalty Among Telephone Mobile Subscribers in Kenya - Metobo Joseline Kwamboka; Timothy Sulo; Michael Korir (European Scientific Journal, ESJ, 2018)
The specific objective of this study was to establish the moderating effect of brand architecture on tangibles and customer loyalty in the mobile telecommunications industry in Kenya. This study adopted an explanatory survey design. The telecom mobile subscribers of the four telecom mobile providers, (Safaricom, Airtel, Telecom Kenya Limited (Orange), and Essar (YU), in Western Kenya formed the target population. The study targeted all mobile service subscribers of Eldoret town who total over 306,683. The study used stratified and systematic sampling designs and a sample size of 400 subscribers was used. The data for this study was collected by use of questionnaires. Moderated regression analysis was used to test the moderating effect of brand architecture on the relationship between tangibles and customer loyalty. Before brand architecture was introduced into the relationship, it was established that tangibles determine customer loyalty of mobile subscribers of telecom mobile providers. The results, after the introduction of brand architecture into the relationship, were that there was both a positive effect and a negative effect. With the introduction of the moderator variable only the item “my service provider’s physical activities are visually appealing” had a significant effect on customer loyalty. The recommendations of the study are that while deciding on the physical activities the telecom mobile providers should see to it that the materials are appealing, their employees are neat and that materials associated with the service (such as pamphlets etc.) are visually appealing. All those have a bearing on customer loyalty. Telecom mobile providers should mind the structure of their products because it has a bearing on the already built customer loyalty. This study will be significant to service providers and policy makers.